KONTRIBUSI DAN TIPOLOGI PEMIKIRAN HADIS MUHAMMAD DAILAMY DALAM BIDANG HADIS DI JAWA TENGAH - Diyan Faturahman; Nur Kholis (Profetika: Jurnal Studi Islam, 2020)
Research on hadith figures has not been done much, even though their contribution in preserving the source of the second Islamic law is very much. Muhammad Dailamy is one of the most influential hadith figures in Central Java. In this research, it will be explained about the contribution and typology of thought of his hadith. This research is a type of qualitative research. In collecting data, researchers used the interview method with a semi-structured interview technique. The data obtained is processed and analyzed using descriptive-analytical methods. In addition, tShe data sources used also include Dailamy’s own intellectual work and other literature relating to research objects, both from books, journals, and internet media. Furthermore, to find out the typology of thought of his hadith, researchers used a theory built by M. Syuhudi Ismail about the typology of thought and understanding of textual-contextual hadith. The results showed that Muhammad Dailamy’s contributions in the field of hadith were among others preachers who had considerable influence in the community, especially in the Purbalingga, Purwokerto, Banyumas, Banjarnegara and surrounding areas. Since 1990 he has been active as a presenter of the Mutiara Pagi program at RRI Purwokerto station. In addition, he is also productive in making of books in the form of study series. Then in understanding the traditions of Muhammad Dailamy it can be classified as a typology of contextual flow. This can be marked by his statement that the understanding of Muslim hadith number 106 about isbal must know the existing context